Al-Masudi’s Historiographical Method: An Empirical and Multidisciplinary Approach in Classical Islamic Historiography - Saputri Saputri; Achiriah Achiriah (Warisan: Journal of History and Cultural Heritage, 2026)
Al-Masudi (d. 956 CE), best known for Muruj al-Dhahab wa Maadin al-Jawhar (The Meadows of Gold and Mines of Gems), occupies an important position in the development of classical Islamic historiography. This study examines the historiographical method employed by Al-Masudi and evaluates its contribution to historical writing in the medieval Islamic world. Using the historical method through the stages of heuristics, source criticism, interpretation, and historiography, the research analyzes methodological features reflected in his major works. The findings indicate that Al-Masudi adopted an empirical, multidisciplinary, and comparative approach to historiography by combining observations derived from extensive travel with critical engagement with transmitted reports. His method incorporated geographical, ethnographic, and environmental perspectives within a thematic framework (al-tasnif al-mawdhu'i), allowing for a broader interpretation of historical phenomena. His engagement with diverse civilizations is reflected in his efforts to document and compare the customs, beliefs, and social practices of different societies rather than confining his narratives to a single cultural perspective. The study argues that Al-Masudi’s historiographical approach represents an important development within the Islamic intellectual tradition and continues to offer valuable insights for contemporary discussions on interdisciplinary and empirically informed historical inquiry.